2018
DOI: 10.3389/fneur.2018.00754
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Family Caregiver's Neuroticism and Conscientiousness Personality in Relation to Quality of Life of Patient With Parkinson's Disease: A Cross-Sectional Study Neuroticism and Conscientiousness Personality in Relation to QoL of Patient With PD

Abstract: Background: Personality impacts life expectancy and comprehensive treatment efficacy for patients with Parkinson's disease (PD). However, current research fails to involve the family caregiver's personality despite significant external support provided by family caregivers. This study explored neuroticism and conscientiousness personality factors of the patient and family caregiver associated with quality of life (QoL) of PD patients.Methods: 134 couples of patients presenting with PD and their family caregive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
(22 reference statements)
0
10
0
1
Order By: Relevance
“…44 Ma et al examined the personality factors of neuroticism and conscientiousness of persons with PD and their caregivers and the association with quality of life of PD patients. 45 Among 134 couples, they found a significant association between neuroticism and the physical or mental status of people with PD. This result partially supports our finding that neuroticism was correlated with depression in caregivers of people with PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Ma et al examined the personality factors of neuroticism and conscientiousness of persons with PD and their caregivers and the association with quality of life of PD patients. 45 Among 134 couples, they found a significant association between neuroticism and the physical or mental status of people with PD. This result partially supports our finding that neuroticism was correlated with depression in caregivers of people with PD.…”
Section: Discussionmentioning
confidence: 99%
“…This result partially supports our finding that neuroticism was correlated with depression in caregivers of people with PD. 45 Another study found that nonmotor psychological symptoms of persons with PD have a much greater impact on caregiver depression than the motor symptoms of persons with PD. 46 However, a meta-analysis study showed a contradictory finding that motor symptoms of people with PD had the strongest relationship with caregiver distress.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the facet "conscientiousness" could influence higher treatment adherence. Furthermore, the caregiver's conscientiousness could have a significant influence on treatment outcome [22]. Self-efficacy mediated the effect of extraversion and conscientiousness on health-related quality of life [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Such reconceptualization can help to foster more compassion and empathy in the caregivers towards the care recipients, thus reducing the caregivers’ abusive impulses. Second, considering that caregivers with high neuroticism may develop negative affect (i.e., frustration, sadness, anger, and emotional instability) when caregiving-related stress accumulates and intensifies [50], behavioral activation methods can be employed to specifically reduce avoidant coping and promote problem-focused coping to help caregivers to stay resilient and emotionally stable when these stressful triggers occur [56]. Further, recent intervention strategies have shown that improvement in positive reinterpretation, perceived control, and perceived social support and decrease in perceived criticism effectively reduced avoidant coping and bolstered problem-focused coping when encountered stressors [48].…”
Section: Discussionmentioning
confidence: 99%
“…Our study attempts to address this gap by showing that although no significant association was evident at baseline, a high level of neuroticism at baseline in caregivers was associated with an increased degree of care neglect during the 2-year observation period. Perhaps, caregivers high in neuroti- cism tend to be more reactive to care-related stressors arising from caregiving activities, which might further lead to distraction in care provision [50]. Additional evidence suggested that individuals high in neuroticism were more likely to adopt avoidant coping strategies when encountered stressors [51], potentially increasing the risk of neglectful behaviors in the caregiving process.…”
Section: Discussionmentioning
confidence: 99%